2016
DOI: 10.5812/ircmj.41939
|View full text |Cite
|
Sign up to set email alerts
|

Successful Repair of Diabetic Foot Ulcer with Honey-Based Treatment: A Case Report

Abstract: Introduction: As a common diabetic complication, foot ulcers may cause a huge burden both on the patient and healthcare system. The current study aims at investigating the effectiveness of honey dressing in the presence or absence of olive oil in diabetic foot ulcer. Case Presentation: The study attempted to report a 70-year-old female with the history of diabetes undergoing high doses of oral antidiabetes drugs (OADs). Following a car accident, she developed a neuropathic ulcer categorized as Wagner grade-II.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
0
8
0
3
Order By: Relevance
“…O mel também pode ser um curativo aceitável para feridas crônicas, pois foi demonstrado repetidamente atividade bacteriostática (Diehr, Hamp, & Jamieson, 2007), mesmo em baixas concentrações, pode impedir o crescimento de vários micro-organismos (Delshad;Tavakkoli-kakhki, & Motavasselian, 2017). Ele é higroscópico, pode desidratar bactérias e seu alto teor de açúcar causa inibição do crescimento bacteriano (Leaper et al, 2012).…”
Section: Resultsunclassified
“…O mel também pode ser um curativo aceitável para feridas crônicas, pois foi demonstrado repetidamente atividade bacteriostática (Diehr, Hamp, & Jamieson, 2007), mesmo em baixas concentrações, pode impedir o crescimento de vários micro-organismos (Delshad;Tavakkoli-kakhki, & Motavasselian, 2017). Ele é higroscópico, pode desidratar bactérias e seu alto teor de açúcar causa inibição do crescimento bacteriano (Leaper et al, 2012).…”
Section: Resultsunclassified
“…In another report of a case series, Mohamed et al examined the effect of honey dressing on the healing of diabetic foot, pain, and cost of dressing, and found that honey has a significant impact on improving diabetic foot; consequently, pain and costs of healthcare were decreased considerably 16. The healing properties of honey can be explained by its antimicrobial and anti-inflammatory effects, moisturizing in the wound bed, osmotic effects, decreasing edema in the cells of the wound, accelerating the process of angiogenesis and granulation in the wound, accelerating collagenases and epithelialization in the wound, increasing activities of lymphocytes and phagocytes, and accelerating debridement of necrotic tissue 11,16–18…”
Section: Discussionmentioning
confidence: 99%
“…Penyakit Diabetes mellitus (DM) merupakan penyakit yang disebabkan karena adanya kelainan metabolisme, yaitu defisiensi insulin sel β di pankreas, resistensi hormon insulin, atau disebabkan oleh kedua-duanya (Delshad et al, 2017). Berdasarkan data International Diabetes Federation 2019 (IDF 2019), 8,9% orang dewasa berusia 20-79 tahun di dunia menderita DM (IDF, 2019).…”
Section: Pendahuluanunclassified